What Motivates Moderation? Policy Shifts of Ruling Parties, Opposition Parties and Niche Parties. Issue 2 (2nd July 2016) - Maeda, Ko
Abstract : What makes political parties moderate their policy platforms? Previous research has emphasised such factors as electoral systems, past election results and changes in voters' preferences as influencing the policy positions that parties take. This study considers a variable that has been ignored in the literature: whether a party is in power or in opposition. I argue that the behaviour of opposition parties stems from their powerless status and their desire to change this status (unless they are niche parties that tend to stick to their positions). It is expected that non-niche opposition parties are more likely to moderate their policy positions than ruling parties or niche opposition parties. A statistical analysis provides strong supportive evidence for the hypothesis.